2007
DOI: 10.1080/01446190600693450
|View full text |Cite
|
Sign up to set email alerts
|

Strategic analysis of large local construction firms in China

Abstract: The many transitory changes in China have raised the intensity level of competition among construction firms. Despite having a high growth economy, some construction firms continue to suffer from low profitability. Meanwhile, practical cases and empirical findings related to Chinese construction firms remain lacking. This research develops a conceptual model for improving the competitiveness of large construction firms in China. The model integrates two main streams of strategic management theories—the industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…To achieve success in the international construction market, CCFs need to upgrade their organizational capabilities through operations in new countries and markets. Cheah et al (2007) identified seven strategic fields and two internal mechanisms of organization for large global engineering and construction firms. These issues exist at the corporate level and are embedded in the very lifeblood of the organization, and hence reflect the corresponding firm-specific resources and capabilities.…”
Section: Core Capability and International Competitivenessmentioning
confidence: 99%
“…To achieve success in the international construction market, CCFs need to upgrade their organizational capabilities through operations in new countries and markets. Cheah et al (2007) identified seven strategic fields and two internal mechanisms of organization for large global engineering and construction firms. These issues exist at the corporate level and are embedded in the very lifeblood of the organization, and hence reflect the corresponding firm-specific resources and capabilities.…”
Section: Core Capability and International Competitivenessmentioning
confidence: 99%
“…The suitability of the factors considered is then analyzed through the evaluation of the model presented in this research. (Cheah, Kang, & Chew, 2007) (Mandal, Howell, & Sohal, 1998) (Shen, Lu, Shen, & Li, 2003) (Shen, Lu, & Yam, 2006) (Venegas & Alarcón, 1997) Corporate Image…”
Section: Literature Review Factors In Construction Companiesmentioning
confidence: 99%
“…This 7 points scale allows statistical efficiency at the time of evaluating (Buckingham & Saunders, 2004). This type of scale has been widely used in similar researches (Cheah et al, 2007;Luu, Kim, Cao, & Park, 2008).…”
Section: Field Studymentioning
confidence: 99%
“…The competitive performance was often measured by the business volume (including sales, profit) (Cheah et al, 2007), efficiency (productivity, return on equity, net profit) (Davies and Walters, 2004), business growth and sustainable growth (Fu et al, 2002). In this research, sales growth and profit growth were used for measuring construction SMEs' competitiveness.…”
Section: Firm's Performancementioning
confidence: 99%